AS ARTES VISUAIS AFRODESCENDENTES CONTEMPORÂNEAS: o ensino- aprendizagem da arte e a Lei Nº 10.639/2003 nos espaços educacionais. - SILVA, Andréa Luisa Frazão (2018)
The research is about Afrodescendent Visual Arts and about the application of methodological proposals in the educational spaces of the Basic Education Unit Father João Miguel Mohana and the Florescer Youth Center, in the implementation of Law 10.639 / 2003. For that, the application of the proposals titled Erêzando and Oris in the educational spaces with discussions on identity and difference based on the works of Afro-descendant artists, seeking to understand how the Afro-Descendant Visual Arts can be an instrument of (re) knowledge and strengthening identity and self-esteem. The theoretical and conceptual discussion of Afro-Brazilian and Afro-Descendant Visual Arts arises with the presentation of a brief historiographic course on the production of Afro-descendant artists from Modernism (20th century) to contemporary (21st century) in the History of Art in Brazil. The study explains the Law No. 10.639 / 2003 as well as guiding documents in which the implementation of education is placed. This is a research on Art, exploratory-descriptive character, multiple case study, having as instruments of data collection the observation and the questionnaire. Thus, through the experiences of applying the methodological proposals on contemporary Afro-Descendant Visual Arts, it was possible to understand how important this theme is for the education and valorization of differences based on a multicultural view of teaching-learning in Art, so that students can enjoy, contextualize, reflect and produce from afrodescendent artistic references. The research reiterates the importance of Art-education, based on criticality and ethno-racial diversity, with the main point being methodological proposals that strengthen the value of the afrodescendant artist to implement Law 10.639 / 2003.